PENGARUH PISANG AMBON PADA PASIEN HIPERTENSI TERHADAP MENURUNKAN TEKANAN DARAH DI RUANG RAWAT INAP RUMAH SAKIT AMINAH KOTA TANGERANG - Kurnia Novianda; Lam Murni Sagala (Universitas Pahlawan Tuanku Tambusai, 2022)
Blood pressure is the pressure of the blood flowing in the arteries when our heart beats, usually 60 to 70 times in 1 minute while at rest (sitting or lying down) blood is pumped to and through the arteries. The purpose of this study was to determine the effect of consuming Ambon bananas on reducing blood pressure in the inpatient room of Aminah Hospital, Tangerang City. Method. This type of research is quantitative using quasi-experimental methods with one group pre-test post-test design, the sampling technique uses total sampling technique. The population in this study were all hypertensive patients in the inpatient room of Aminah Hospital, Tangerang City, namely a total population of 15 respondents. Data collection used an observation sheet with the paired sample t-test data analysis method. the results of the systolic blood pressure t-test before and after being given therapy showed a p-value of 0.000. This means that Ambon bananas can significantly reduce systolic and diastolic blood pressure in people with hypertension. Giving ambon bananas before breakfast in people with hypertension can reduce blood pressure. Keywords: Ambon Banana, Blood Pressure, Hypertension